Exploring mobile health service adoption among diabetic patients using an integrated UTAUT-PMT model - Ragil Saputra; Satriyo Adhy; Hasbi Yasin (Bulletin of Electrical Engineering and Informatics, 2026)
Mobile health services (MHS) have emerged as vital tools for delivering accessible and cost-effective healthcare, particularly for managing chronic conditions such as diabetes. This study investigates the behavioral factors influencing MHS adoption by integrating the unified theory of acceptance and use of technology (UTAUT) and protection motivation theory (PMT) into a unified model. A total of 189 valid responses were collected through both offline surveys (23 diabetic outpatients from 4 clinics) and online surveys (166 members of an Indonesian diabetes forum). Structural equation modeling was used to test the proposed relationships. The results show that self-efficacy (SE), effort expectancy (EE), and perceived vulnerability (PV) significantly influence behavioral intention (BI), while BI strongly affects MHS usage behavior (UB). Conversely, perceived severity (PS) and response cost (RC) were not significant. The study offers a novel theoretical contribution by demonstrating how the interaction between cognitive and motivational factors affects technology adoption in healthcare. Practical implications are provided for app developers and policymakers to improve MHS engagement through personalized interventions.